People's knowledge assessment about infertility among community in Taman Balok Pine, Kuantan, Pahang - Abdullah, Sinan Mohammed; Sulaiman, Saidatul Farhah (2014)
There is a perception that the prevalence of infertility is on the rise since the knowledge about infertility is still inadequate in many parts of the world. Another important source of misinformation that could influence fertility self-care is erroneous belief, e.g. infertility myths or fertility increases by staying healthy. The aim of this study is to assess people’s knowledge about fertility and focusing on identifying the type of information needed to educate people about the potential risks for infertility. The research had been investigated in three areas of knowledge namely risk factors associated with infertility (e.g. smoking), beliefs in false fertility myths (e.g. benefits of rural living) and beliefs in the benefits of healthy habits (e.g. exercising regularly). A total of 145-sample size was taken from both genders whether married or unmarried in theaverage age 18 years old and above. The community-based crosssectional by using self-administer questionnaires had been conducted. Knowledge scores were range from zero to 100%, that are good knowledge (>75%), the average knowledge (50%-75%) and poor knowledge (<50%). The results demonstrated that the participants were knowledgeable about the risk factors for infertility but were not as knowledgeable at recognizing factors that had on fertility (myths and healthy behaviors), and believed that these factors actually increased a chance for getting pregnant. This study can be conclude that the planners and program managers of healthcare professionals were able to design appropriate strategies for better understanding regarding the knowledge of infertility causes, perception towards infertility especially belief in the myths and also prevent the belief about taking healthy habits will not lead to infertility.